Introduction to the Special Issue—Cardiothoracic Surgical Critical Care: A Future of Distinction - Amar M. Bhatt; Michael K. Essandoh (Medicina, 2022)
Critical care after cardiothoracic surgery is an inseparable component of any successful surgical program addressing intrathoracic pathologies, including heart failure treatment with mechanical circulatory support, and respiratory failure requiring extracorporeal membrane oxygenation (ECMO) therapy [...]